Design and Development of a QR Code-Based Ordering System and Mobile Cashier Application at Rumah Seduh Coffee Shop - Fadhilah, Indirokan; Rindri, Yang Agita; Wathan, M. Hizbul (STMIK KHARISMA Makassar, 2025)
This research was carried out with the aim of designing and developing a QR Code–based ordering system integrated with a mobile cashier application at Warung Kopi Rumah Seduh. The previously manual process created several issues, including long queues, delayed service, and frequent transaction recording errors that disrupted operational efficiency. To address these challenges, a digital system was introduced that allows customers to place orders independently by scanning a QR Code, with the orders being automatically recorded in the cashier system. The mobile cashier application supports real-time order processing, transaction management, and structured sales data storage. The system was developed using a prototyping approach, beginning with requirements analysis through field observations and user interviews. The implementation results demonstrate that this solution improves service efficiency, accelerates the ordering process, reduces input errors, and enhances the organization of sales data. Ultimately, this study is expected to provide practical contributions for MSMEs in adapting to the challenges of service digitalization.